2022
DOI: 10.1111/joie.12287
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Preferencing in Markets with Vertically Integrated Gatekeeper Platforms*

Abstract: The competitive strategies of 'gatekeeper' platforms are subject to enhanced scrutiny. For instance, Apple and Google are being accused of charging excessive access fees to app providers and privileging their own apps. Some have argued that such allegations make no economic sense when the platform's business model is to sell devices. In this paper, we build a model in which a gatekeeper device-seller facing potentially saturated demand for its device has the incentive and the ability to exclude from the market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Specifically, it charges a fee f i to R i for each unit sold through its web site. Following a recent literature (e.g., Etro, 2021;Padilla et al, 2022), we assume throughout that consumers can purchase retailers' products only through P's web site-that is, P is a gatekeeper platform (Alexiadis & de Streel, 2020)-or, more generally, they compete with each other only on the e-commerce marketplace owned by P-for example, as in Baye and Morgan (2001), they are monopolists in different (offline) local markets.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it charges a fee f i to R i for each unit sold through its web site. Following a recent literature (e.g., Etro, 2021;Padilla et al, 2022), we assume throughout that consumers can purchase retailers' products only through P's web site-that is, P is a gatekeeper platform (Alexiadis & de Streel, 2020)-or, more generally, they compete with each other only on the e-commerce marketplace owned by P-for example, as in Baye and Morgan (2001), they are monopolists in different (offline) local markets.…”
Section: Modelmentioning
confidence: 99%
“…See, for example, Etro (2021), Anderson and Bedre‐Defolie (2021), and Hagiu et al (2022), who study the welfare implications of allowing e‐commerce platforms to sell private labels on their marketplaces, and Padilla et al (2022), who examine the circumstances under which a platform can use self‐preferencing to foreclose third‐party sellers. Unlike the present paper, these articles focus on platforms' strategies and their welfare implications under the assumption of sellers' competition in the marketplace.…”
mentioning
confidence: 99%
“…On the theory side, Aridor and Gonçalves (2022) study the conditions under which a self-preferencing platform is welfare improving. Padilla et al (2022) look at the conditions that make self-preferencing more likely, and De Corniere and Taylor (2014) show how integrated platforms (search engines) might be expected to distort rankings (search results). In addition, there are papers that consider platforms' profit incentives in relation to RSs absent vertical integration.…”
Section: Existing Economics Literaturementioning
confidence: 99%
“…Also, Zhu and Liu (2018) and Wen and Zhu (2019) empirically found that the possibility of entry of a platform into the seller's product space itself reduces the innovation incentive of third-party sellers. In addition, Jorge Padilla and Piccolo (2022) assumed the durable device market and the non-durable service market, and suggested that abuse of market power by gatekeeper platforms may result in harm to consumers and that the loss of consumer surplus may become greater as the degree of saturation of the device market increases. Moreover, anti-competitive impacts of self-preferencing behavior-that is, a platform prominently features its own products rather than competitors' products-have also been analyzed in several papers including Colomo (2020), de Sousa (2020) and Marty (2020).…”
Section: Introductionmentioning
confidence: 99%